Dietary supplementation with standard ileum digestible lysine in starter period improves male broiler growth weight - NASR, JAVAD; PARVIZ, MEHDI (The Indian Journal of Animal Sciences, 2015)
This research evaluates standard ileum digestible (SID) lysine density in starter period in Ross 308 male broilers to better understand the impact of increase dietary SID lysine density in live weight performance. Six diets (6 replicates) in starter period with different levels of SID lysine density, 1.411% (150% NRC), 1.321% (140% NRC), 1.215% (130% NRC), 1.126% (120% NRC), 1.035% (110% NRC) and 0.945 (100% NRC, 1994) were used in a completely randomized experimental design. All diets were iso-caloric and iso-nitrogenous. As a result of this study, Broilers fed 1.321% SID lysine level diet, body weight in 21 d was increased by 90 g compared with standard group (P